Use of the Third Person for Self-Reference by Jesus and Yahweh: A Study of Illeism in the Bible and Ancient near Eastern Texts and Its Implications for Christology - Elledge, Roderick (The Library of New Testament Studies, 2017)
Cover -- Contents -- List of Tables -- Acknowledgments -- Abbreviations -- Chapter 1 -- Introduction -- Thesis -- Methodology -- History of Research -- Chapter 2 -- Illeism in Classical Antiquity -- Early Evidence -- Ancient Historians -- Conclusion -- Chapter 3 -- Illeism in the Old Testament -- Deferential Use -- Within an Oath Formula -- Summons to Listen -- Characterization of the Speaker -- Within a Trial Setting/Historical Context -- In the Speech of Kings -- King David -- In the Speech of Yahweh -- Conclusion -- Chapter 4 -- Illeism in Ancient Near Eastern Texts -- Illeism in the Speech of Gods of the ANE -- Illeism in the Speech of Kings of the ANE -- Deferential Use of Illeism in the ANE Texts -- Conclusion -- Excursus: Deity of Kings and Kingship of Gods -- Chapter 5 -- Illeism in the New Testament -- Illeism in Paul's Letters -- The Illeism of Jesus -- Conclusion -- Chapter 6 -- Summary and Conclusions -- Summary -- Conclusions -- Appendix -- 1. Illeisms of Yahweh in Construct -- 2. Evaluated Illeisms of Yahweh -- 3. Illeism of Jesus by Book -- 4. Occurrences of Biblical Illeism by Person -- Bibliography -- Author Index -- Index of Texts.